AHMADIYAH DALAM LABIRIN SYARIAH DAN NASIONALISME KETUHANAN DI INDONESIA (UINSI Samarinda, 2015)
This paper aims at looking at the phenomenon of intolerance against Jemaat Ahmadiya in Indonesia that has been occuring since several decades ago. The Jemaat Ahmadiya is continuously accused of blaspheming Islam, and, thus, led to its dissolution by the government. Employing political sociology as an approach, this article frames the plight of Jemaat Ahmadiyya through the lens of Jeremy Menchik’s “godly nationalism”. It then argues that (1) violence against Jemaat Ahmadiya are not only perpetrated by certain elements of intolerance society, but also accommodated by the government thanks to the general consensus regarding the common orthodox theism in Indonesia; (2) the phenomenon of intolerance also shows that Indonesian citizens are still perplexed by the concept of nationalism: on the one hand, Indonesia is deemed to be a secular state, on the other hand, it accommodates religions and their teachings into the state’s life.